Respuesta :

Answer:

One Solution

(2, 1)

Step-by-step explanation:

We have the following system of equations

[tex]x+4y = 6\\y=2x-3[/tex]

To solve the system, substitute the second equation in the first equation and solve for the variable x

[tex]x+4(2x-3) = 6[/tex]

[tex]x+8x-12 = 6[/tex]

[tex]9x = 6+12[/tex]

[tex]9x = 18[/tex]

[tex]x = \frac{18}{9}[/tex]

[tex]x = 2[/tex]

Now substitute the value of x into any of the two equations and solve for the variable y.

[tex]y=2(2)-3[/tex]

[tex]y=4-3[/tex]

[tex]y=1[/tex]

Finally the system of equations has one solution

(2, 1)

ACCESS MORE